2011
DOI: 10.1093/ecam/neq075
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Oil Alleviates MAPKs‐ and IL‐6‐mediated Diabetes‐related Cardiac Hypertrophy in STZ‐induced DM Rats

Abstract: Garlic oil has been reported to protect the cardiovascular system; however, the effects and mechanisms behind the cardioprotection of garlic oil on diabetes-induced cardiaomyopathy are unclear. In this study, we used streptozotocin (STZ)-induced diabetic rats to investigate whether garlic oil could protect the heart from diabetes-induced cardiomyopathy. Wistar STZ-induced diabetic rats received garlic oil (0, 10, 50 or 100 mg kg_1 body weight) by gastric gavage every 2 days for 16 days. Normal rats without dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…Consistent, with this view, we found that pretreatment of cardiomyocytes with pharmacological blockers for H 2 S and NO significantly, blocked the anti-hypertrophic action of both garlic skin and flesh extracts. Based on our result we speculate that, upregulation of H 2 S and NO may be mediating some of the mechanisms underlying the antihypertrophic action of garlic observed in earlier studies conducted on animal models of cardiac hypertrophy induced by hypertension [9] and diabetes [8]. …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Consistent, with this view, we found that pretreatment of cardiomyocytes with pharmacological blockers for H 2 S and NO significantly, blocked the anti-hypertrophic action of both garlic skin and flesh extracts. Based on our result we speculate that, upregulation of H 2 S and NO may be mediating some of the mechanisms underlying the antihypertrophic action of garlic observed in earlier studies conducted on animal models of cardiac hypertrophy induced by hypertension [9] and diabetes [8]. …”
Section: Discussionsupporting
confidence: 60%
“…However, there is no information on the potential of garlic skin; a papery covering surrounding the individual cloves and a by-product of garlic processing. There are only two reports on the effectiveness of garlic in preventing the development of cardiac hypertrophy in animal models of hypertension and diabetes [8,9] however, the mechanisms underlying garlic effects are not explored. Lastly, no study has examined the potential of a variety of hard necked Rocambole purple garlic developed in Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that garlic oil attenuates the impaired cardiac contractility [23, 24]. Other studies reported that allicin protected cardiac function and prevented the development of cardiac hypertrophy through ROS-dependent mechanism involving multiple intracellular signaling (ERK1/2, JNK1/2 and PI3/Akt/GSK3 β signaling pathways) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have demonstrated that these polysulfides release H 2 S in vivo (32) and that they exert cardioprotective potential therapeutic effects via the release of H 2 S (12,44,55). In fact, there are several articles in the literature reporting the beneficial effects of garlic extracts in various models of diabetic complications and wound healing (2,11,18,50). However, in these studies the specific role of H 2 S as a mediator of these therapeutic actions remains to be investigated.…”
Section: Conclusion and Therapeutic Implicationsmentioning
confidence: 99%